Material culture and cultural identity : a study of Greek and Roman coins from Dora - Motta, Rosa Maria, (Archaeopress archaeology., 2015)
The ancient harbour town of Dor/Dora in modern Israel has a history that spanned from the Bronze Age until the Late Roman Era. The story of its peoples can be assembled from a variety of historical and archaeological sources derived from the nearly thirty years of research at Tel Dor - the archaeological site of the ancient city. Each primary source offers a certain kind of information with its own perspective. In the attempt to understand the city during its Graeco-Roman years - a time when Dora reached its largest physical extent and gained enough importance to mint its own coins, numismatic sources provide key information. With their politically, socio-culturally and territorially specific iconography, Dora's coins indeed reveal that the city was self-aware of itself as a continuous culture, beginning with its Phoenician origins and continuing into its Roman present.